2014
DOI: 10.1021/es4052999
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Avoidance of Potential Artifacts and Misinterpretations in Nanomaterial Ecotoxicity Measurements

Abstract: Novel physicochemistries of engineered nanomaterials (ENMs) offer considerable commercial potential for new products and processes, but also the possibility of unforeseen and negative consequences upon ENM release into the environment. Investigations of ENM ecotoxicity have revealed that the unique properties of ENMs and a lack of appropriate test methods can lead to results that are inaccurate or not reproducible. The occurrence of spurious results or misinterpretations of results from ENM toxicity tests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
219
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(222 citation statements)
references
References 220 publications
(409 reference statements)
2
219
0
1
Order By: Relevance
“…The NP dispersion step of the protocol is not precisely defined and the timing between the dispersion step and the dosing step is not specified, which can influence the extent of agglomeration during the exposure or the structure/composition of the protein corona. If variable precipitation of the NP agglomerates occurred during the separate rounds, the cells may have been effectively exposed to different dosing conditions (Petersen et al, 2014). Improved dispersion procedures or the use of more automation in preparing the dosing plate could reduce the variability observed within the laboratory when using NH 2 -PS NP and serum.…”
Section: Discussionmentioning
confidence: 99%
“…The NP dispersion step of the protocol is not precisely defined and the timing between the dispersion step and the dosing step is not specified, which can influence the extent of agglomeration during the exposure or the structure/composition of the protein corona. If variable precipitation of the NP agglomerates occurred during the separate rounds, the cells may have been effectively exposed to different dosing conditions (Petersen et al, 2014). Improved dispersion procedures or the use of more automation in preparing the dosing plate could reduce the variability observed within the laboratory when using NH 2 -PS NP and serum.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most advanced instrumentation platforms used for these types of studies are costly and of limited accessibility (Szakal et al, 2014). As such, a multidisciplinary and orthogonal approach is needed, including the development of new or hybridized measurement techniques, in order to promote the understanding of ENMs-crop interactions (GardeaTorresdey et al, 2014;Petersen et al, 2014).…”
Section: Perspectives and Research Prioritiesmentioning
confidence: 99%
“…However, results from toxicological studies, such as measurements of their cell toxicity, often differ substantially among laboratories and have questionable reliability (1)(2)(3). Moreover, numerous studies have identified artifacts (i.e., incorrect test results) during nanoecotoxicology studies as a result of the unique behaviors of ENMs (3). One important aspect of experimental design is the inclusion of control experiments to identify potential artifacts and increase reliability of the test results.…”
Section: Introductionmentioning
confidence: 99%
“…This information is modified from a recent publication on the avoidance of artifacts and misinterpretations in nanoecotoxicology testing, and the reader is referred to that manuscript for a more complete discussion of this topic (3). While many of these same control experiments are relevant for measurements on the potential human health impacts of ENMs, the focus in this protocol is on measurements of potential ecological effects.…”
Section: Introductionmentioning
confidence: 99%